Bibliometric study on the utilization of sorafenib in hepatocellular carcinoma - Meng, Wenjun; Luo, Yihang; Zhao, Lu; Zhang, Yaoyu; Liu, Jiyan; Li, Shadan; Du, Yang; Li, Hongshuai (Frontiers in Oncology, 2024)
BackgroundAlthough the number of studies on sorafenib for hepatocellular carcinoma (HCC) is increasing during the past two decades, no detailed scientometric examination of its knowledge framework has been undertaken. Therefore, we performed a bibliometric analysis on this topic.MethodsVOSviewer and CiteSpace were utilized to analyze the articles regarding sorafenib for HCC from 2005 to 2024, which were retrieved from the Web of Science Core Collection (WoSCC) database.ResultsThere were 7,667 articles related to sorafenib in HCC were retrieved from the WoSCC database, and they covered 99 countries/regions, 5,640 institutions, and 30,450 authors. The most published literature of countries and institutions were China and Sun Yat-sen University, respectively. Cancers is the journal with the most papers published in this field, and the journal with the most co-citations is N Engl J Med. Among authors, Masatoshi Kudo has published the most research papers, and the most co-citations go to JM Llovet. The keywords “survival”, “apoptosis”, “efficacy”, “transarterial chemoembolization”, “lenvatinib”, etc. represent the current hotspots in this field.ConclusionsWe identified current hotspots and trends by bibliometric analysis in sorafenib-HCC field, which might provide valuable guidance for future researches. Further explorations are supposed to conduct the continued study of HCC apoptosis, large-scaled clinical trials with international cooperations, and comprehensive treatments including multiple systemic or locoregional approaches in patients with HCC.